Elaboration of a proposal for the creation of a Business Incubator focused on Gastronomic Projects - Ricaurte Párraga, Rossana María; Plaza Zúñiga, Daniel Alejandro (Ingeniería Química y Desarrollo, 2023)
The proposal of this work is based on a new business model based on the Canvas methodology, this is due to the high impact that incubators have in the economic area of the countries, this model focuses on providing support in gastronomic projects that are start your operations. To carry out this project, tools such as surveys, interviews, focus groups will be used, in order to carry out statistical data in which we can see the interest of the entrepreneur to carry out his project in a more stable way and what is the opinion of it. In order to achieve this objective, a structure was implemented in which the business model used in the creation of the company that focuses on incubation projects in the gastronomic sector was developed.
Keywords: Incubator; entrepreneurship; gastronomy; business model; innovation